Construção e avaliação de indicadores de sustentabilidade para a agricultura familiar: uma análise multidimensional - Stoffel, Jaime Antonio (2014)
The main goal of this thesis is to analyze the sustainability of family farming, through proposition and evaluation of indicators and indexes regarding economic, social, environmental and institutional dimensions. The study was carried out in the county of Francisco Beltrão, in the southwest region of Paraná state, specifically in the watershed of Jacaré River. The rural area of the watershed has 33 headquarters of agricultural ownership, being all of them characterized as family farming. When it comes to socioeconomic context, Southwest region of Paraná represents considerably the agricultural sector, and more specifically, family farming, which is present in all counties, accounting for around 90% of the sector. Methodologically eight indicators of sustainability for each dimension were selected, reaching a total of thirty-two indicators within the four analyzed dimensions. The information to calculate the indicators of sustainability was collected among the family farmers in the studied watershed, and also among the involved agents. This research aimed to know how human actions have affected their surroundings, regarding the risks of their stay, surviving in the medium and long run, as well as by making the best political decisions, through institutional environment. Initially, the Sustainability Indicators (SI) were calculated for each of the proposed dimensions and in each of the different ways of analyzed productive organizations (agricultural, dairy and integrated). Through the indicators, the other indexes that complement the study came out. Among them there are: Individual Sustainability Index (ISI); Specific Sustainability Index (SSI); Specific General Sustainability Index (SGSI); and Total Sustainability Index (TSI). It was noticed that the model developed and applied in the study proved to be able to answer the questions and the problems raised by the present research, through multidimensional analysis. Besides showing the reality of the agricultural properties which are part of the environment of the studied area intra-dimensionally, it also showed the relations of this reality inter-dimensionally. This way, it is possible to face sustainability individually, but especially, in the context of agricultural properties as a whole.